2017
DOI: 10.2217/imt-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Two is Better Than One: Advances in Pathogen-Boosted Immunotherapy and Adoptive T-Cell Therapy

Abstract: The recent tremendous successes in clinical trials take cancer immunotherapy into a new era and have attracted major attention from both academia and industry. Among the variety of immunotherapy strategies developed to boost patients' own immune systems to fight against malignant cells, the pathogen-based and adoptive cell transfer therapies have shown the most promise for treating multiple types of cancer. Pathogen-based therapies could either break the immune tolerance to enhance the effectiveness of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Notably, IL-10 is abundantly produced in healthy persons ( 14 ). Xin et al ( 15 ) identified that IL-10-producing TFH cells have an increased capacity to form stable TFH-B cell conjugates compared with their IL-10-TFH counterparts, suggesting that IL-10 + TFH cells may specialize in providing distress signals to B cells during chronic infection. Importantly, depletion of IL-10 + /IL-21 + -coproducing CD4 + T cells or deletion of IL-10, specifically from TFH cells, resulted in impaired GC B cell responses, lymphocytic choriomeningitis virus-specific antibody production and viral control ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IL-10 is abundantly produced in healthy persons ( 14 ). Xin et al ( 15 ) identified that IL-10-producing TFH cells have an increased capacity to form stable TFH-B cell conjugates compared with their IL-10-TFH counterparts, suggesting that IL-10 + TFH cells may specialize in providing distress signals to B cells during chronic infection. Importantly, depletion of IL-10 + /IL-21 + -coproducing CD4 + T cells or deletion of IL-10, specifically from TFH cells, resulted in impaired GC B cell responses, lymphocytic choriomeningitis virus-specific antibody production and viral control ( 16 ).…”
Section: Discussionmentioning
confidence: 99%